Cx31.1 can selectively intermix with co-expressed connexins to facilitate its assembly into gap junctions - Leighton, Stephanie E.; Wong, Robert S.; Lucaciu, Sergiu A.; Hauser, Alexandra; Johnston, Danielle; Stathopulos, Peter B.; Bai, Donglin; Penuela, Silvia; Laird, Dale W. (Journal of cell science, 2024)
Connexins are channel-forming proteins that function to facilitate gap junctional intercellular communication. Here, we use dual cell voltage clamp and dye transfer studies to corroborate past findings showing that Cx31.1 (encoded by GJB5) is defective in gap junction channel formation, illustrating that Cx31.1 alone does not form functional gap junction channels in connexin-deficient mammalian cells. Rather Cx31.1 transiently localizes to the secretory pathway with a subpopulation reaching the cell surface, which is rarely seen in puncta reminiscent of gap junctions. Intracellular retained Cx31.1 was subject to degradation as Cx31.1 accumulated in the presence of proteasomal inhibition, had a faster turnover when Cx43 was present and ultimately reached lysosomes. Although intracellularly retained Cx31.1 was found to interact with Cx43, this interaction did not rescue its delivery to the cell surface. Conversely, the co-expression of Cx31 dramatically rescued the assembly of Cx31.1 into gap junctions where gap junction-mediated dye transfer was enhanced. Collectively, our results indicate that the localization and functional status of Cx31.1 is altered through selective interplay with co-expressed connexins, perhaps suggesting Cx31.1 is a key regulator of intercellular signaling in keratinocytes.